Studi Perbandingan Kemampuan Menghafal al-Qur’an dengan Metode Kaisa dan Metode Wafa dalam Menghafal al-Qur’an pada Anak Usia Dasar di Rumah Tadabbur Qur’an (RTQ) Kendari - Hasri, Kharis Sulaiman; Hasridan, Kharis Sulaiman (Prodi Pendidikan Agama Islam - Fakultas Agama Islam ( FAI ), 2019)
The purpose of this study was to determine the differences in the ability to memorize the santri Qur'an (middle chilhood) at the Rumah Tadabbur Qur’an (RTQ) of Hombis in Kendari city both before and after the kaisa method and the wafa method were applied. This study uses a quantitative research method with an experimental approach.The results of this study were obtained that; (1) There was no difference in the ability to memorize the Qur'an before being given the Kaisa method and Wafa's method. This is evidenced by the significance value of 0.889> α = 0.05 so that H0 is accepted (2) There is a positive and significant difference in the ability to memorize the Qur'an before and after being given the Kaisa method treatment. This is evidenced by the significance value of 0,000 <α = 0.05 so that H0 is rejected (3) There is a positive and significant difference in the ability to memorize the Qur'an before and after being given Wafa method treatment. This is evidenced by the significance value of 0,000 <α = 0.05 so that H0 is rejected (4) There is a positive and significant difference in the ability to memorize the Qur'an after being treated by the Kaisa method and the Wafa method. This is evidenced by the significance value of 0.02 <α = 0.05 so that H0 is rejected.